MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN AKTIVITAS MATA PELAJARAN IPAS MENGGUNAKAN MODEL PBL, NHT, DAN TGT PADA PESERTA DIDIK KELAS IV SEKOLAH DASAR - Mutiara Sahda; Radiansyah (STKIP Subang, 2024)
The problems identified in this study are the lack of activities and critical thinking skills possessed by students. This is because learning only flows in one direction, minimal student involvement, lack of application of learning models, and boring learning. The use of Problem Based Learning, Number Head Together, and Team Game Tournament learning strategies will help you solve this problem. This study seeks to highlight teacher activities and investigate ways to improve learning objectives, critical thinking skills, and student involvement. Three classroom action research (CAR) meetings have been carried out. Twenty-one students from class IV B at SDN Kebun Bunga 4 Banjarmasin became the subjects of the study during the second semester of the 2023–2024 academic year. The conclusion of this study explains how educators aged between 24 and 30 years work to meet the